Short antibiotic treatment followed by regular administration of acid suppressant (proton pump inhibitor) reduce AB42 load in the brain and in the gut. (20th December 2022) - Chevalier, Claire; Marizzoni, Moira; Tournier, Benjamin; Paquis, Arthur; Gueorguiev, Boris R; Millet, Philippe; Frisoni, Giovanni B
Abstract: Background: Fecal microbiota transplantation (FMT) from healthy mice, microbiota depletion with antibiotic treatment (ABT) or with germ free mice have been associated with a reduction of cerebral amyloid load in Alzheimer's disease (AD) mice models, indicating that the gut microbiota can modulate amyloid load in the brain. Interestingly, amyloid can also deposit in the gut, particularly within proximity to vasculature, nerves, and nerve plexuses. Additionally, acid suppressant drug such as proton pump inhibitors (PPI) have been shown to modify the gut microbial population. Here we postulate that ABT+PPI could modulate the gut microbiota and amyloid load in the gut and in the brain. Method: Sixty female, two‐year old 3xTg mice (APP SWE, PS1 M146V and Tau P301L ) were divided in 2 groups and received: (1) 2‐weeks of ABT to deplete the microbiota followed by recurrent PPI administration simultaneously with (FMT) once a week for 2 months or (2) FMT only at same frequency. The FMTs consisted in i) water, ii) litter mate mice and, iii) bacteria isolated from 1 young and 1 cognitively unimpaired elderly donor to test different microbiota. Result: After 60 days of treatment, Ab42 and Ab40 were measured by ELISA in the hippocampus and the colon. We observed that ABT‐PPI treatment reduced the soluble and insoluble form of Ab42 in the hippocampus (ANOVA p<0.05) and, interestingly, also in the colon (ANOVA p<0.05), independently of the microbiota transplanted. This was specific to the Ab42 isoform as no differences was observed in the levels of AB40. Conclusion: The results suggest that ABT‐PPI can reduced Ab42 in the brain as well as in the gut in an AD mice model, independently of the microbiota transplanted. The link between the amyloid in the gut and in the brain remain a black box. More research is needed to rule out that the Ab detection in the gut is not due to randomly deposited circulating amyloid from blood. Also, the short ABT intervention and the 2 months delay before sample collection suggests that the driver of the effect observed is the PPI. This will be confirmed by testing the administration of PPI only.